Growth in Commuting Patterns and Their Impacts on Rural Workforce and Economic Development. Issue 1 (February 2023) - Kures, Matt; Deller, Steven C.
Residential and employment locational decisions for working households are frequently commingled. Numerous economic and social factors like job accessibility, wage differentials, housing markets, travel time, trip-chaining opportunities, dual employment, and other quality-of-life considerations influence where a household ultimately chooses to reside relative to places of employment. These choices in turn shape commuting patterns within a region. Using the U.S. Census Bureau's LEHD Origin-Destination Employment Statistics (LODES), the authors explore longitudinal changes in the growth of commuting patterns based on commuters traveling 50 miles or more between their place of residence and place of employment for counties in Midwestern states from 2002 to 2019. The authors find that the rate of commuters traveling 50 miles or more appears to have increased in rural areas across several periods and regions. Thus, rural communities concerned about labor supply constraints must take into consideration more expansive geographic labor markets and approach labor force development in partnership across local economic development institutions. In essence, the growth in commuting sheds requires stronger regional partnerships to address the issue.